A study on the effectiveness of online banking services in Malacca / Nur Shazlin Jamaludin - Jamaludin, Nur Shazlin (Faculty of Business and Management, 2011)
This research is to identify the factors that influence the online banking to become more effectiveness by the users from IPK Melaka and to identify the most influencer that help online banking to be more effective in services by using online banking services. About 100 of questionnaires were distributed by hand to selected staffs and officers at IPK Melaka. The research findings show that the most factors influenced online banking to become more effective among the staffs and officers in IPK Melaka was the technology that has been used in banking business. As a conclusion, the results of the findings that include the analysis of the demographic profile, general information of respondents and the most factors that influence effectiveness towards internet banking by staffs and officers at IPK Melaka. From the findings, the researcher had come out with several recommendations that bank need to updates and innovate better services in terms of graphic and displays of to give the customer choices to use online banking easily and individual clients should be familiar with the computer literate and English language. Lastly, the government must take part and support this kind of services to give customer a self-confidence to use the services provided by each bank in Malaysia. Through this kind of supporting, the users feel that they’re protected financially. So that, online banking services can be more effectiveness through meet the customers’ preferences.